2010
DOI: 10.1111/j.1474-9726.2009.00545.x
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous glucocorticoids decrease skeletal angiogenesis, vascularity, hydration, and strength in aged mice

Abstract: SummaryAging or glucocorticoid excess decrease bone strength more than bone mass in humans and mice, but an explanation for this mismatch remains elusive. We report that aging in C57BL ⁄ 6 mice was associated with an increase in adrenal production of glucocorticoids as well as bone expression of 11b-hydroxysteroid dehydrogenase (11b-HSD) type 1, the enzyme that activates glucocorticoids. Aging also decreased the volume of the bone vasculature and solute transport from the peripheral circulation to the lacunar-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
233
0
9

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 249 publications
(258 citation statements)
references
References 54 publications
16
233
0
9
Order By: Relevance
“…We have shown previously that blockade of glucocorticoid action on osteoblasts and osteocytes blunts the loss of bone mass and strength caused by aging in mice (50). We also noted in those studies that corticosterone levels in the circulation increase with age.…”
Section: Discussionmentioning
confidence: 59%
“…We have shown previously that blockade of glucocorticoid action on osteoblasts and osteocytes blunts the loss of bone mass and strength caused by aging in mice (50). We also noted in those studies that corticosterone levels in the circulation increase with age.…”
Section: Discussionmentioning
confidence: 59%
“…The significance of HIF-1α is also evident from the fact that administration of ethyl 3,4-dihudroxybenzoate (EDHB) deters the progression of SANFH because it inhibits the functioning of HIF prolyl hydroxylase and it stabilizes HIF-1α expression (1,30,31). A target gene of HIF-1α, VEGF, also plays a major role in encouraging the angiogenesis-osteogenesis coupling process (32)(33)(34). VEGF improves angiogenesis by activating a variety of signal pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier work from our group and others has shown that an increase in endogenous GCs and inflammatory cytokines contributes to the age-associated loss of bone mass and strength (6,11). Moreover, administration of GCs or an endogenous rise in TNF␣ has been causally linked to increased osteoclast numbers, decreased osteoblast numbers, and bone loss (1,50).…”
Section: Discussionmentioning
confidence: 99%
“…We and others have shown that GCs or TNF␣ increase osteoblast and osteocyte apoptosis. Importantly, bone fragility induced by chronic GC excess is due, to a large extent, to increased osteocyte apoptosis and results from cell autonomous effects (6,56). In view of this evidence, we have searched here for a mechanism linking ROS to the pro-apoptotic actions of GCs and TNF␣.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation